EVALUASI FAKTOR EKOLOGI DAN DISTRIBUSI KERANG SENTENG (Placuna placenta) DI MUARA SUNGAI BELA KABUPATEN INDRAGIRI HILIR PROVINSI RIAU - Isma, Muhammad Fauzan; Nasution, Syafruddin; Tanjung, Afrizal (Jurnal Perikanan dan Kelautan, 2015)
The research was conducted on January 2015, in the waters of the Sungai Bela Estuary,Indragiri Hilir Regency, Riau Province. The research purposed was to define the habitatcharacteristics, vertical distribution, and analysis of correlation between habitat parameters andabundance of windowpane oyster (Placuna placenta). There were 4 stations and each stationdivided into 3 sampling points based on the depth, they were <2 meter, 2–4 meter, and >4meters. Results shown that good habitat characteristics for windowpane oyster was ontemperature of 27.77 0C, Total Suspended Solid on 24.33 mg/L, current speed on 0.02 m/s, pHon 7.87, salinity on 20.60/00, DO on 7.63 mg/L, BOD on 4.17 mg/L, Nitrate on 0.07 mg/L,phosphate on 0.05 mg/L, and organic on 30.07%. The highest abundance of windowpane oysterwas on station 4 (11.000 Ind/Ha). While in vertical term, the highest abundance was at <2meter depth. The distribution pattern of windowpane oyster was evenly at station 1 andclumped in station 2, 3 and 4. Result of correlation abundance of windowpane oyster effect oncurrent speed was r= -0.711, pH was r= 0.649, the abundance of phytoplankton was r= 0.688,and mud substrate was r= 0.535.